Pentalogy of Fallot in a Siberian Husky Bitch: Clinical-Pathological Alterations - Barros, Vitor Eduardo Arantes de; Bombardelli, Monique Machado Louredo; Sales, Filipe Augusto; Rodrigues Ribeiro, Rafaela; Donizeti Damasceno, Adilson; Alves Carvalho, Rosângela; Brianezi Dignani de Moura, Veridiana Maria (Acta Scientiae Veterinariae, 2026)
Background: Pentalogy of Fallot (PF) is a rare form of cyanotic congenital heart disease characterized by several anatomic defects, including the presence of a ventricular septal defect, pulmonary stenosis, overriding aorta, right ventricular hypertrophy, and an atrial septal defect. These alteration can lead to clinical signs directly related to pulmonary stenosis severity, that may include hypoxia, dyspneia, cyanosis, growth delay, syncope, weight loss, ascites an sudden death. PF also predisposes patients to severe thromboembolic events. This report describes the clinical and pathological findings in a young bitch with PF, focusing on cardiopulmonary thromboembolic events as well as renal changes. Case: A 5-month-old bitch Siberian Husky with a history of progressive respiratory distress, tachypnea, fatigue at rest, and exercise intolerance over the past 2 months was diagnosed with PF after clinical evaluation revealed muffled heart sounds in both mitral and tricuspid focus, and echocardiography display of several alterations such as perimembranous ventricular communication, right ventricular hipertrophy, ostium secundum interatrial communication, tricuspid regurgitation, aorta destraposition and pulmonary stenosis. The interventricular communication flow was diverted from the right ventricle to the aorta. Blood tests revealed polycithemia and severe hypoxemia, that were considered complicating factors. The dog received clinical treatment with atenolol, enalapril and omega 3 until 8 months of age, and subsequently underwent a modified Blalock-Taussig shunt procedure. A systemic-pulmonary bypass leading from the left subclavian artery to the aorta was made in order to improve lungs blood flow. Surgery recommendation was based on clinical signs aggravation to cyanotic crises. After procedure was treated with heparin at hospital, followed by clopidogrel, and atenolol, for treatment maintenance at home. Fourteen days later, the patient experienced respiratory collapse and died, after pulmonary thromboembolism. Pathological examination revealed a communication between the aorta and pulmonary artery, graft thrombosis, and pulmonary thromboembolism. The kidneys showed areas of infarction macroscopically, with tubular degeneration and necrosis microscopically. Discussion: The histopathological changes related to the patient’s death are likely resulted from hypoxia, turbulent blood flow, and hyperviscosity syndrome due to severe polycythemia. This alterations could be related to PF predisposition to thromboembolic events associated with a inefficient antithrombotic therapy in the post-operatory period, even with the heparin continuous infusion treatment and blood flow reestablishment. However, even with surgery dogs with PF usually present a poor prognosis, as well as median life expectation of 2 years with pharmacological treatmentand 6 years with surgery. Proper monitoring and adjustment of treatment protocols are essential to improve outcomes and reduce the risk of severe complications in similar cases. Furthermore, adequate management of predisposing factors and antithrombotic therapy is considered essential for patients with PF. Keywords: Fallot tetralogy, tromboembolic disease, hyperviscosity syndrome, Blalock-Taussing modified Título: Pentalogia de Fallot em uma cadela Husky Siberiana: alterações clínico-patológicas Descritores: Tetralogia de Fallot, doença tromboembólica, síndrome da hiperviscosidade, Blalock-Taussing modificada.